Australian industrial relations in 2017. (June 2018) - Wright, Chris F
This article introduces the Journal of Industrial Relations Annual Review of Industrial Relations in 2017. It discusses the Fair Work Commission's decision to reduce Sunday and public holiday penalty rates for workers in the retail and hospitality industries, the growing problem of low wages, and the Turnbull government's policy changes relating to the employment of temporary migrant workers. It then provides an overview of the other articles contained in the Annual Review issue.